A tuffaceous volcaniclastic turbidite bed of Early Miocene age in the Temburong Formation of Labuan, North‐West Borneo and its implications for the Proto‐South China Sea subduction in the Burdigalian. (29th January 2021) - Burley, Stuart D.; Breitfeld, H. Tim; Stanbrook, David 'Stan'; Morley, Robert J.; Kassan, Jochen; Sukarno, Mohamad; Wantoro, D. Wantoro
Abstract: A 2 m thick bed of smectite‐rich clay within a sequence of distal deep water turbidites and marine mudstones of the Temburong Formation on the island of Labuan, Sabah, North‐West Borneo, is an altered, re‐sedimented pyroclastic tuff which is geochemically of rhyolite‐dacite composition. The tuff bed was deposited in deep water, although probably <1, 000 m, by traction currents and retains relic siliceous shards, feldspar phenocrysts and biotite crystals but was dominated by ash‐grade material. The tuff is interpreted as a turbidite deposit and most probably records long distance sub‐marine transport down the depositional slope from an active volcanic system in the hinterland. It has a zircon U–Pb weighted mean age of 19.6 ± 0.1 Ma whilst combined forminiferal and nannofossil ages from the enclosing marine mudstones range from 21.5 to 19.4 Ma; together these indicate an early Miocene age for the Temburong Formation. The tuff is the result of a very short‐lived volcanic arc magmatic episode and was either related to similar aged volcanics of the Sintang Suite in central Borneo or a product of the Proto‐South China Sea subduction beneath the Cagayan arc north‐east of Borneo. The age indicates that deep water sedimentation in North‐West Borneo continued into the Burdigalian suggesting the subduction trench of the Proto‐South China Sea was active into the early Miocene, beneath the depocentre of the Temburong turbidite fan. By contrast, sandstones representative of the typical marine Temburong Formation yield abundant zircons which are dominately Cretaceous in age indicating an important switch in source provenance during the Early Miocene from the Crocker Formation that is dominated by Permian‐Triassic zircons. This difference in zircon populations likely reflects an important tectonic event in the early Miocene that resulted in uplift of central Borneo to supply sediment to the Sabah Trough whilst the input of material derived from the western terrains diminished. The Temburong Formation was sourced by reworking of uplifted Rajang Group, Sapulut or Trusmadi formations. Abstract : A smectite bed in a sequence of distal, deep water turbidites and marine mudstones of the Temburong Formation on the island of Labuan, Sabah, North‐West Borneo is interpreted as an altered, re‐sedimented pyroclastic tuff which is geochemically of dacite‐rhyolite composition. The tuff is interpreted as a turbidite deposit and records long distance sub‐marine transport down the depositional slope from an active volcanic system in the hinterland. It has a zircon U–Pb weighted mean age of 19.6 ± 0.1 Ma whilst combined forminiferal and nannofossil ages from the enclosing marine mudstones range from 21.5 to 19.4 Ma. The tuff is the result of a very short‐lived volcanic arc magmatic episode and was either related to similar aged volcanics of the Sintang Suite in central Borneo or a product of the Proto‐South China Sea (PSCS) subduction beneath the Cagayan arc north‐east of Borneo. The age indicates that deep water sedimentation in North‐West Borneo continued into the Burdigalian suggesting the subduction trench arc of the PSCS was active into the early Miocene.